Kekerabatan Bahasa Melayu Ujung Gading Kecamatan Lembah Melintang dan Bahasa Mandailing Air Bangis Kecamatan Sungai Beremas Kabupaten Pasaman Barat - Zri Andayani; Ermanto (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
The benefits of this research are (1) to determine the proportion of the degree of kinship between the two languages ​​being studied (2) to determine the length of time the separation between the two languages ​​is being studied (3) to find out the sound correspondence between the languages ​​being studied. Comparative history of linguistics is the type of research used. Next, qualitative and quantitative are the methods used by the researcher. The object of this research is the Malay language which originates from Nagari Ujung Gading which is in the Lembah Melintang sub-district and the Mandailing language in the Nagari Air Bangis area which is in the Sungai Beremas sub-district, West Pasaman Regency. The information in this research is the cognate vocabulary of two hundred basic Swadesh vocabulary and three hundred cultural vocabulary from the two languages ​​that will be studied. Recording equipment/cameras and stationery are research instruments. Proficiency procedures (fishing method and conversant methods) and advanced methods (advanced proficient engagement methods and note-taking methods) are procedures and methods for providing data in research. The method used to analyze information is a lexicostatistical method with a glottochronology method. Based on calculations and research data using lexicostatistical techniques, it was found that related vocabulary in the Malay language in the Ujung Gading area, which is in the Lembah Melintang sub-district, and the Mandailing language in the Air Bangis area, which is in the Sungai Beremas sub-district, to be precise, in the West Pasaman Regency, is 242 words cognat (relatives) and then 258 words are not. cognate. So, the proportion level of kinship between the two languages ​​is 41.5%. Furthermore, based on the calculation of the glotochronological method, it was found that the separation of the two languages ​​was 2027 years ago. Based on the five hundred vocabularies found sound correspondences, there are 103 vocabularies of similar or identical forms, 79 selected sound/phoneme vocabulary, 47 sound/phoneme absorption vocabulary, and 13 sound/phoneme accumulations that correspond to sound.